Social Media Addiction and its Impact on Social Relationships - Ahnan, Maftuh; Budi, Lalu Agung Purnama; Roziqin, Mohamad Firzon Ainur; Rosalia, Nur; Sasono, Rian Ari (Association for Scientific Computing Electrical and Engineering, 2022)
Social media is a platform that allows users to engage in activities and collaborate. Social media can make communicating with fellow humans easier via a smartphone connected to an internet connection. But on the other hand, the presence of social media can have a negative impact. Excessive use of social media can be addicting and can have a negative repercussion on one's social relationships. Therefore, this paper will analyze the relationship between social media addiction on social relationships and how it impacts one's social relationships. To analyze that, a research instrument in the form of a questionnaire was used. After that, the validity and reliability tests were carried out regarding the questionnaire. If the questionnaire passed the test, the questionnaire was distributed. The results from the questionnaire were analyzed by an assumption and hypothesis test respectively,, to describe the objectives of this study.